Strategi Koping Pada Remaja dengan Kecenderungan Berperilaku Agresif - Rochwidowati, Novia Sinta; Rismarini, Nadya Anjani (Universitas Islam Negeri Raden Intan Lampung, 2019)
Agression among teenagers, including bullying, school gangsters, and even students criminality, has been an issue for years. On the other hand, teenagers are expected to adapt well in society, to make healthy social relations, in order to become healthy and responsible adults. These developmental task takes a capability to adapt and overcome problems in everyday life, which is defined as coping strategy. This study aims to investigate the relationship between coping strategy and agrressive behavior in teenagers using Coping Strategy Scale for Teenagers and Aggressive Behavior Scale. The subjects were 416 students of middle and high schools in Bantul, Yogyakarta. Data were analyzed using Product Moment correlation test. The result showed that there was a negative correlation between coping strategy and aggressive behavior in teenagers (r= -0,287; p<0,01). Teenagers who had better ability to cope with stressful events demonstrated less aggressive behavior.